Cytostatic effect of xanthone-loaded mPEG-b-p(HPMAm-Lac 2) micelles towards doxorubicin sensitive and resistant cancer cells - Khonkarn R. (2014)
Xanthone exhibits several medicinal activities and especially it inhibits the growth of cancer cells. However, the use of xanthone is limited because of its low aqueous solubility and systemic toxicity. In the present study xanthone was loaded into poly(ethylene glycol)-b-poly[N-(2-hydroxypropyl) methacrylamide-dilactate] mPEG-b-p(HPMAm-Lac 2) micelles in order to overcome these drawbacks. It was shown that xanthone could be loaded in these micelles up to 2mg/mL with ∼100% entrapment efficiency and ∼20% loading capacity. The average particle diameter of the xanthone loaded mPEG-b-p(HPMAm-Lac 2) micelles as determined by dynamic light scattering ranged from 84 to 112nm. In vitro assays showed that xanthone in its free form as well as loaded in polymeric micelles had a high cytotoxicity towards both doxorubicin sensitive and, importantly, resistant cancer cells. On the other hand empty mPEG-b-p(HPMAm-Lac 2) micelles did not show any cytotoxicity towards normal cells (PBMCs). Interestingly, the cytostatic effect of xanthone towards normal cells was masked when loaded in the micelles. The mechanism of cell growth inhibition by xanthone-loaded polymeric micelles was mediated through induction of apoptosis, as evidenced from a subdiploid peak of propidium iodide stained cells using flow cytometric analysis. From the results of this study it can be concluded that xanthone has potent anticancer activity not only on sensitive but also on doxorubicin resistant cancer cell lines. mPEG-b-p(HPMAm-Lac 2) micelles are therefore attractive delivery systems of xanthone for the treatment of cancer. © 2012 Elsevier B.V.